Micropropagation of Andrographis Paniculata - Lin, Mei Sun (2015)
Andrographis paniculata belongs to Acanthaceae family. A. paniculata is a herbaceous plant that can be found in both tropical and subtropical countries. It is also a medicinal plant and possesses high medicinal values. Therefore, the objectives of this study were to determine the germination rate of the seed of A. paniculata and the effects of different concentrations of indolc-3-butyric acid (IBA) and zeatin on the growth of A. paniculara. In this experiment, seeds of A. paniculara were grown in vitro on the Murashinge and skoog (MS) medium. After that, the cotyledonary leaves of this plant were subcultured on MS medium supplemented with 0, 1.0, 2.0, 3.0, 4.0 and 5.0 mg/L zeatin and IBA in single exposure or in combination and observed for multiple shoots and roots formation over a period of 8 weeks. Highest shoot formation and highest root formation was produced in MS medium supplemented with single exposure of 5.0 mg/L zeatin and 5.0 mg/L IBA respectively. Zeatin and IBA in combination was found to produce callus. Micropropagation could serve as an alternative reproduction system for A. paniculata.